2015
DOI: 10.1038/srep08194
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Confirmation Study of GWAS-Identified Genetic Variants for Kawasaki Disease in A Chinese Population

Abstract: Genome-wide association studies (GWASs) have identified multiple single nucleotide polymorphisms (SNPs) associated with Kawasaki disease (KD). In this study, we replicated the associations of 10 GWAS-identified SNPs with KD in a Han Chinese population. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by logistic regression, and cumulative effect of non-risk genotypes were also performed. Although none of the SNPs reached the corrected significance level, 4 SNPs showed nominal associations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
(68 reference statements)
3
21
0
Order By: Relevance
“…For example, Khor and colleagues reported that the allele A of the polymorphism rs1801274 contributed to elevated KD risk [22], and similar findings have also been achieved by Onouch and colleagues [19]. Besides, Lou and colleagues exhibited nominally reducing tendency for AG þ GG vs. AA and GG vs. AA in their study [26]. While Kwon and colleagues claimed that significant correlation of the polymorphism with KD onset only appeared in males, not among females [29].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…For example, Khor and colleagues reported that the allele A of the polymorphism rs1801274 contributed to elevated KD risk [22], and similar findings have also been achieved by Onouch and colleagues [19]. Besides, Lou and colleagues exhibited nominally reducing tendency for AG þ GG vs. AA and GG vs. AA in their study [26]. While Kwon and colleagues claimed that significant correlation of the polymorphism with KD onset only appeared in males, not among females [29].…”
Section: Discussionsupporting
confidence: 61%
“…During the fulltext screening, 14 more publications were further omitted for not conforming to our inclusion criteria. As a result, 11 eligible reports were ultimately encompassed into this meta- analysis [19][20][21][22][23][24][25][26][27][28][29], containing 17 independent studies. Of the studies, 13 were on Asian populations while only 4 on Caucasians.…”
Section: Yields Of Literature Searching and Selectionmentioning
confidence: 99%
“… 23 Several genome-wide association studies have revealed common variants that strongly associated with KD, CAL formation, and IVIG treatment. 24 – 26 Here, we applied a GWAS-based weighted genetic risk score (wGRS) to develop a genetic model to predict the IVIG resistance in KD.…”
mentioning
confidence: 99%
“…Although the efforts to find a causative microorganism have failed [2][3][4] , the suspicion of an association between some unidentified microorganism and Kawasaki disease remains [4][5][6][7] . Investigations to identify a genetic susceptibility locus in Kawasaki disease also have been performed recently [8][9][10] . Several institutes had cooperated and reported a result regarding the genetic susceptibility of Kawasaki disease [11] .…”
Section: Introductionmentioning
confidence: 99%